Fenotipos clínicos en pacientes con enfermedad pulmonar obstructiva crónica (EPOC) por humo de cigarrillo y por exposición a humo de biomasa atendidosen el Hospital Regional Docente de Trujillo - Carrión Yupanqui, Alan Yván (2017)
Cigarette smoke and biomass are the main risk factors for chronic obstructive pulmonary disease (COPD). The clinical phenotypes of COPD were proposed due to they have therapeutic and prognosic repercussions. Objective: To determine the proportion of clinical phenotypes in patients with COPD caused by cigarette smoke and biomass, treated at the Trujillo Regional Hospital. Materials and Methods: It’s been realized a cross-sectional descriptive study. 35 medical records were reviewed, in patients with diagnosis of COPD due to cigarette smoke and biomass, It’s been determined which clinical phenotype they belonged to and the proportion of each phenotype according to exposure. Results: 5 (14.29%) patients were classified within the COPD group by cigarette smoke and 30 (85, 71%) in the biomass group. The chronic bronchitis phenotype was presented in 31.43%, of which 33.33% were by biomass smoke and 20% by cigarette. The overlap EPOC-asthma phenotype represented 25.71%, of which 26.67% were due to biomass smoke and 20% for cigarette smoke. The emphysema phenotype was presented in 42.86%, where 40% were due to biomass smoke and 60% by cigarette smoke, there wasn't significative difference in the groups, χ2 = 0.716 p = 0.69. Conclusion: The presentation rate of the clinical phenotypes of COPD in both groups is varied, there wasn't significative difference in the distribution